Carbon Price Impacts on the Chinese Tourism Industry. (February 2021) - Meng, Samuel; Pham, Tien; Dwyer, Larry; Grant, Bligh
This study simulates the short-run effects of an Emissions Trading Scheme (ETS) and two auxiliary policies on the Chinese tourism industry. The results show that the ETS alone will increases energy prices and have significant adverse impacts on China's economy. The adverse impacts are relatively stronger on the energy sectors than they are on tourism. Two auxiliary policies—a tourism subsidy and a reduced goods and services tax (GST)—are examined as policy options to soften the negative impacts of the ETS. Results show that the tourism-subsidy policy is more effective than the GST reduction policy.